REDESIGN OF THE PALEMBANG HOUSING COMPLEX IN BUKIT KECIL DISTRICT, PALEMBANG CITY WITH A BIOPHILIC ARCHITECTURE APPROACH - Titi Zahwa Alfira Rokan; Moch. Fathoni Setiawan; Lulut Indrianingrum (Universitas Negeri Semarang, 2025)
High-rise flats are a form of vertical housing built as a solution to meet the housing needs of the community, especially low-income communities, as well as an effort to prevent the growth of slums in urban areas. The 24 Ilir Housing Complex in Bukit Kecil District, Palembang City, is a vertical housing complex located in a very strategic location in the city centre. However, it has experienced a decline in environmental quality, building functionality, aesthetic value, population density, and suboptimal utility systems. These conditions have resulted in a low quality of life for residents and the formation of an uninhabitable residential environment. This paper aims to formulate a concept for the redesign of housing complex through the application of biophilic architecture principles as a design approach to improve the quality of housing and the environment. The research method used is descriptive through literature study, observational study, and field study. This method uses primary and secondary data analysis covering functional, biophilic, technical, performance, and architectural aspects. The redesign idea results in improvements in spatial layout, utility systems, and social interaction among residents. The author's conclusion in this idea shows that the biophilic architecture approach is effective as a strategy for redesigning urban flats to maximise natural resources around the flats, improve the quality of life with the natural environment, and enhance the well being of residents.